The role of antioxidants in the prevention of cardiovascular disease - Vukomanović, Predrag; Petrović, Bojana; Daskalović, Branislava; Vukomanović, Marija (Archives of Pharmacy, 2022)
Cardiovascular diseases (CVD) are the leading cause of death and disability worldwide, with a greater impact on the quality of life and shortening life expectancy. Owing to the organized preventive measures, there has been a reduction in CVD mortality rates in developed countries. Over the past few decades, epidemiological studies have shown that the intake of fruits and vegetables, which are rich in vitamins and antioxidants, significantly reduces the risk of CVD and has a protective role in their prevention. Oxidative stress has been linked to the pathogenesis of many CVD diseases (ischemic heart disease, atherosclerosis, hypercholesterolemia, diabetes, and hypertension). LDL in the subendothelial space, under conditions of oxidative stress, undergoes oxidation, resulting in its oxidized form, which is one of the key molecules in the promotion of the inflammatory process in the blood vessel wall. Antioxidants protect cells in various ways, by blocking the initial synthesis of free radicals, eliminating existing free radicals, repairing cell damage, or inhibiting apoptotic cell death. The most important antioxidants: selenium, vitamin E, β-carotene, vitamin C, carotenoids, flavonoids, and other plant polyphenols are the body’s basic defense against the negative effects of free radicals. Their concentration in the body depends on a diet that must be varied and balanced to meet daily needs. In cases of malnutrition, malabsorption, or increased needs, dietary supplements and pharmaceutical preparations are recommended. However, all antioxidant preparations, including those for the prevention of cardiovascular diseases, should not be a substitute for proper nutrition and a healthy lifestyle.